2014
DOI: 10.1016/j.jmaa.2014.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Polygonal equalities and virtual degeneracy inLp-spaces

Abstract: Suppose 0 < p ≤ 2 and that (Ω, µ) is a measure space for which Lp(Ω, µ) is at least twodimensional. The central results of this paper provide a complete description of the subsets of Lp(Ω, µ) that have strict p-negative type. In order to do this we study non-trivial p-polygonal equalities in Lp(Ω, µ). These are equalities that can, after appropriate rearrangement and simplification, be expressed in the formwhere {z 1 , . . . , zn} is a subset of Lp(Ω, µ) and α 1 , . . . , αn are non-zero real numbers that sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…By Lennard et al [25], this implies that (Z, d) has p-negative type for some p ∈ (1,2]. Consequently, the metric transform (T, √ d p ) embeds isometrically into 2 by Kelleher et al [20,Theorem 5.6]. We conclude that the only metric trees that satisfy condition (2) are those of generalised roundness one.…”
Section: Embedding Properties Of Metric Trees Of Generalised Roundnesmentioning
confidence: 63%
See 2 more Smart Citations
“…By Lennard et al [25], this implies that (Z, d) has p-negative type for some p ∈ (1,2]. Consequently, the metric transform (T, √ d p ) embeds isometrically into 2 by Kelleher et al [20,Theorem 5.6]. We conclude that the only metric trees that satisfy condition (2) are those of generalised roundness one.…”
Section: Embedding Properties Of Metric Trees Of Generalised Roundnesmentioning
confidence: 63%
“…The proof of Theorem 5.2 shows that all metric trees have strict 1-negative type. Therefore, every metric tree satisfies Theorem 5.2(1) by the result of Kelleher et al [20].…”
Section: Embedding Properties Of Metric Trees Of Generalised Roundnesmentioning
confidence: 70%
See 1 more Smart Citation
“…This theorem underpins the main considerations of this paper. Theorem 2.3 (Kelleher et al [7]). Let n ≥ 1 be an integer and let X be a real or complex vector space.…”
Section: Signed Simplices and Polygonal Equalities In L P -Spacesmentioning
confidence: 99%
“…For p ∈ (0, 2), Kelleher et al [7] have shown that if a subset B of L p (Ω, µ) is affinely independent (when L p (Ω, µ) is considered as a real vector space), then B has strict p-negative type. The converse of this statement is true when p = 2 but not when p < 2 (see Theorem 2.4 and Remark 1).…”
Section: Introductionmentioning
confidence: 99%